Exploring the Possibility of Peak Individualism, Humanity's Existential Crisis, and an Emerging Age of Purpose - Grant, Gabriel B. (Frontiers in Psychology, 2017)
There is an emerging cultural narrative in the United States that we are entering an age of purpose - that millennials, more than any other generation, are searching for purpose and purposeful work (Sheahan, 2005) and that we are entering an era or economy of purpose (Hurst, 2014). For profit, non-profit, and educational institutions are perceiving and adapting to serve millennials’ demand for purpose in life, specifically within the workplace (Klein, Galinsky, & Grant, 2015). Yet, longitudinal studies of purpose do not exist, and millennials are also referred to as GenMe. Existing quantitative research suggests they (we) are increasingly individualistic, materialistic, and narcissistic (Greenfield, 2013). Google’s digitization of millions of books and the Ngram Viewer allow for quantified analysis of culture over the past two centuries. This tool was used to quantitatively test the popular notion that there is a rise in demand for purpose. Analysis reveals a growing interest in purpose-in-life and a shift toward collectivistic values emerging over the lifespan of the millennial generation.